Cost Analysis of Health Care professionals-Dedicated Portal - Azzouni, Rawand (2011)
This dissertation is an individual effort that is related to a group internship undertaken with Pfizer’s Established Products Business Unit- United Kingdom. It builds on the recommendations made in the internship’s main report and addresses one of the seven proposed e-channels, namely the specialised portal, with HCP as the target audience. The dissertation tries to answer the specific question “How much the HCP-dedicated portal will cost to implement?” In order to answer the question, relevant academic and practitioners’ literature in cost management and estimation is reviewed and used, the relevant data is collected and the actual process of cost estimation is demonstrated. Under appropriate and specific assumptions, the cost of the software implementation of the HCP-dedicated portal will be around $40,000; rounded to the nearest thousand. Both; the managerial implications and limitations of the cost estimation analysis are highlighted.